Profitability and money propagation in communities of bank clients : a visual analytics approach (2020)
We analyze financial transactions of corporate bank clients not only at the level of particular customers, but also at the level of communities of customers and a system as a whole. We first build a structure of communities using the Louvain method, which in turn allows us to estimate the profitability of each community. Then, we visualize the community structure and transaction propagation in a custom-made visual analytic platform. The detection and visualization of communities proved to be extremely valuable in the study of money propagation because it revealed a critical structure and the behavior of the clients.